Flood risk management along German rivers – A review of multi-criteria analysis methods and decision-support systems. Issue 135 (September 2022) - Perosa, Francesca; Seitz, Laura Felicia; Zingraff-Hamed, Aude; Disse, Markus
Abstract: Sustainable and climate-resilient decisions in flood risk management (FRM) are complex problems, which should consider flood mitigation, but also ecological, economic, and social aspects within a collaborative decision-making process. In this article, we explore the state of multi-criteria analysis (MCA) and decision-support systems (DSS) in Germany to understand their advantages, challenges in applicability, and potential for future development. A systematic literature review was conducted to identify peer-reviewed articles and gray literature published from 1990 to 2020, focusing on the use of MCA and DSS for decision-making in FRM and related river management in Germany. The topic reached its peak of publications in the first decade of the 21st century. In terms of used criteria, 27 out of 40 publications consider all main aspects of decision-making in FRM (hydrology/hydraulics, ecology, social, economics). In 25 publications, multiple ecosystem services are concealed in the decision-making by considering, besides flood mitigation, water provisioning, inland navigation, energy, and agricultural production. Issues related to the applicability of MCA and DSS are apparent in the publications. These include the presence of an outdated DSS and the low number of publications (six) presenting adaptation strategies for future applications. Moreover, acceptance of decisions based on MCA and DSS can be harmed by uncertainties and a lack of transparency and participation. Further initiatives that address these issues (participatory planning, consideration of uncertainties, a Germany-wide "general DSS framework" with a legally binding character) would help decision-makers meet holistic, better-accepted, and climate-resilient decisions. Highlights: We analyzed multi-criteria analysis (MCA) and decision-support systems (DSS). German river management seldom uses structured MCA and DSS for decision-making. In 63% of studies, authors mention multiple ecosystem services in decision-making. Lack of transparency and participation affects acceptance of MCA and DSS results. Developing a Germany-wide general DSS framework is a potential future step.